Interpersonal Communication Relasi Dosen Dan Mahasiswa UIN Sumatera Utara Dalam Pembelajaran Public Relations - Siregar, Susilawati; Sazali , Hasan (Jurnal Pekommas, 2024)
interpersonal communication is an important process in exchanging messages, ideas, emotional expressions and information between individuals who interact directly. In an academic context, the implementation of effective interpersonal communication is becoming increasingly important for lecturers and students. This research aims to determine interpersonal communication relations between lecturers and students as well as students' understanding of public relations learning. The researcsh method used is qualitative case studies with data collection techniques through field observations, interviews and documentation. Communication Accommodation Theory is used as a theoretical framework to explain how individuals adjust their communication style in interactions. The research results show that interpersonal communication between lecturers and students at UIN North Sumatra in the context of Public Relations learning is going very well. Lecturers demonstrate high engagement and the ability to create comfortable and responsive interactions, while students respond positively and enthusiastically. The use of body language and effective verbal communication from lecturers enriches students' learning experiences and lecturers are not only communicators but also communication facilitators for students.